World Englishes and creative idioms in English as a lingua franca. Issue 2 (June 2016) - PITZL, MARIE‐LUISE
ABSTRACT: Although language contact is usually long‐term and extensive in the postcolonial contexts of world Englishes, it also takes place in situations where English is used as a lingua franca (ELF) for international communication. The particulars and conceptualization of this transient type of language contact in ELF are the focus of the present paper. Building upon previous studies on the creative use and variation of idioms in ELF, this paper looks at creative idioms in ELF interactions as emblematic instances of such transient language contact and multilingual creativity.